The Impact of Youtube on Mind Mapping Method on Students English Speaking Skills - Nuril Fahmi Ulumiddin; Feri Ferdiyanto; Raudhatul Islam (Attractive : Innovative Education Journal, 2025)
This This study aims to investigate the effect of integrating YouTube with the mind mapping method on students' English-speaking skills. A qualitative descriptive approach was employed, with data collected through observation, questionnaires, and interviews. The participants were seven students from the English Education Study Program at Zainul Hasan Genggong Islamic University who implemented the ABC (Aksi Belajar Cerdas)-based mind mapping method supported by the YouTube platform to enhance their speaking abilities. The findings indicate that the use of YouTube as a supplementary medium in the ABC-based mind mapping method has a positive impact on students’ confidence, fluency, and vocabulary acquisition in spoken English. Additionally, the method fosters greater student engagement and creativity in expressing ideas in a structured manner during classroom discussions. Nevertheless, the study also highlights the potential for distraction when students use YouTube, emphasizing the need for self-awareness and discipline to ensure its effective use for academic purposes. This study contributes to the growing body of research on digital-assisted language learning by demonstrating the effectiveness of combining YouTube with mind mapping techniques to enhance English-speaking skills. It also offers practical recommendations for managing media use in educational settings to maximize learning outcomes.